1984
DOI: 10.1007/bf01908301
|View full text |Cite
|
Sign up to set email alerts
|

Renal nerve and blood pressure responses to stimulation of cardiac receptors in dogs and cats by bradykinin

Abstract: It has been recently demonstrated in anesthetized, sinoaortic denervated-vagotomized (SAD + Vx ) cats that epicardial or intracoronary (IC) bradykinin (BK) evokes an increase in efferent renal nerve activity (RNA) and a pressor response which is mediated by the cardiac sympathetic afferent nerves. The purpose of this study was to compare the effect of epicardial, IC, and left atrial (LA) administration of BK on arterial blood pressure (ABP) and RNA in intact and SAD + Vx cats and dogs. A total of seven cats an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
(34 reference statements)
1
1
0
Order By: Relevance
“…This result is in accord with other reports that showed that bilateral vagotomy does not affect cardiovascular responses induced by bradykinin application to the heart (Gorman et al, 1983;Gorman and Zucker, 1984;Niitani et al, 1988;Veelken et al, 1996) or abdominal visceral organ such as the gallbladder (Longhurst and Ordway, 1983). In contrast bradykinin applied to the heart is known to stimulate cardiac vagal afferents (Kaufman et al, 1980;Hisata et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result is in accord with other reports that showed that bilateral vagotomy does not affect cardiovascular responses induced by bradykinin application to the heart (Gorman et al, 1983;Gorman and Zucker, 1984;Niitani et al, 1988;Veelken et al, 1996) or abdominal visceral organ such as the gallbladder (Longhurst and Ordway, 1983). In contrast bradykinin applied to the heart is known to stimulate cardiac vagal afferents (Kaufman et al, 1980;Hisata et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…Potassium ions always increase heart rate and blood pressure, while bradykinin induces increase and decrease in both heart rate and blood pressure. Gorman et al (1983Gorman et al ( , 1984 showed that changes in heart rate and blood pressure upon epicardial bradykinin stimulation are dependent on the species of animal, with an excitatory response in cats, an insignificant response in dogs, and an inhibitory response in monkeys. Ness and Gebhart (1988) reported that cardiovascular responses to noxious colorectal stimulation are affected by the type of anesthetic used or depth of anesthesia.…”
Section: Discussionmentioning
confidence: 99%